Information Systems Skills Requirements in Malaysia - Ahmad, Rodina; Abu Bakar, Zaitun (Malaysian Journal of Computer Science, 2000)
This paper is based on the findings of a survey carried out on more than 70 organizations in the private and public sectors to investigate the current requirements of information systems (IS) skills in the Malaysian IT community. The survey data was analysed pertaining to seven categories of IS skills. A comparison is made with a similar study carried out in Hong Kong. The findings show that there is an increasing demand for non-technical skills as well as technical skills for IS professionals. Degree programs in the public universities, however, are giving more emphasis on courses, which are more technically oriented. Recommendations are made to these institutions to review their IT curriculum to produce graduates more suited for the industry needs.